Differences in the carcinogenic evaluation of glyphosate between the International Agency for Research on Cancer (IARC) and the European Food Safety Authority (EFSA) - Portier, Christopher J; Armstrong, Bruce K; Baguley, Bruce C; Baur, Xaver; Belyaev, Igor; Bellé, Robert; Belpoggi, Fiorella; Biggeri, Annibale; Bosland, Maarten C; Bruzzi, Paolo; Budnik, Lygia Therese; Bugge, Merete D; et al. (Journal of Epidemiology and Community Health, 2016)
Serious flaws in the scientific evaluation in the RAR incorrectly characterise the potential for a carcinogenic hazard from exposure to glyphosate. Since the RAR is the basis for the European Food Safety Agency (EFSA) conclusion, 4 it is critical that these shortcomings are corrected. [...]the WG also saw a significant increase in the incidence of pancreatic islet cell adenomas in two studies in male Sprague-Dawley rats. 14-16 In one of these rat studies, thyroid gland adenomas in females and liver adenomas in males were also increased.